Enteropathogens Associated with Acute Diarrhea in Children from Households with High Socioeconomic Level in Uruguay. (12th March 2015) - Varela, Gustavo; Batthyány, Lara; Bianco, María Noel; Pérez, Walter; Pardo, Lorena; Algorta, Gabriela; Robino, Luciana; Suárez, Ramón; Navarro, Armando; Pírez, María Catalina; Schelotto, Felipe
Abstract : Infectious diarrhea, a common disease of children, deserves permanent monitoring in all social groups. To know the etiology and clinical manifestations of acute diarrhea in children up to 5 years of age from high socioeconomic level households, we conducted a descriptive, microbiological, and clinical study. Stools from 59 children with acute community-acquired diarrhea were examined, and their parents were interviewed concerning symptoms and signs. Rotavirus, adenovirus, and norovirus were detected by commercially available qualitative immunochromatographic lateral flow rapid tests. Salmonella, Campylobacter, Yersinia, and Shigella were investigated by standard bacteriological methods and diarrheagenic E. coli by PCR assays. We identified a potential enteric pathogen in 30 children. The most frequent causes of diarrhea were enteropathogenic E. coli (EPEC), viruses, Campylobacter, Salmonella, and Shiga-toxin-producing E. coli (STEC). Only 2 patients showed mixed infections. Our data suggest that children with viral or Campylobacter diarrhea were taken to the hospital earlier than those infected with EPEC. One child infected with STEC O26 developed "complete" HUS. The microbiological results highlight the importance of zoonotic bacteria such as atypical EPEC, Campylobacter, STEC, and Salmonella as pathogens associated with acute diarrhea in these children. The findings also reinforce our previous communications about the regional importance of non-O157 STEC strains in severe infant food-borne diseases.